Pengaruh Perhatian Orang Tua Selama Masa Pandemi Covid-19 Terhadap Hasil Belajar Matematika Siswa Kelas IV SD - Yonathan Saba' Pasinggi; Zaid Zainal; A.Nurfauziah (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2022)
The motivation behind this review was to discover the impact of parental consideration during the Covid- 19 pandemic on understudy learning results, which for this situation are 4th grade primary school understudies in Taulan Village, Enrekang Regency. The quantitative approach was picked as the examination approach with ex post facto and correlational sorts. The population in this review was all 4th grade primary school understudies in Taulan Village, Enrekang Regency, adding up to 47 understudies. Computation of the quantity of tests utilizing the Slovin equation (1960) and involving corresponding arbitrary examining as an inspecting strategy in order to acquire an example of 15 understudies from SDN 19 Kabere, 18 understudies from SDN 108 Taulan and 9 understudies from SDN 140 Kabere so the all out example from the three SD Desa Taulan is 42 understudies. To gather information, polls and documentation were utilized to acquire information from the two factors. Information examination utilizes inferential factual investigation, however first it should meet the traditional suspicion test, specifically the ordinaryness test and linearity test. The consequences of the traditional supposition test show that the information is regularly circulated and the connection between factors is direct. The consequences of inferential examination show that the worth of sig. 0.000 (0.000 < 0.05) then, at that point, H0 is dismissed and H1 is acknowledged, so the facts really confirm that understudies' math learning results during the Covid-19 pandemic are impacted by the consideration of their folks and the impact is positive and critical. Keywords: parental consideration, covid-19 pandemic, mathematics learning outcomes